KONSELING PRANIKAH DALAM MEMPERSIAPKAN KELUARGA KRISTEN DI GEREJA KRISTEN SETIA INDONESIA (GKSI) “JEMAAT ISA ALMASIH” TAMAN MINI - Jonidius Illu; Joni Salman Gonto (Jurnal PKM Setiadharma, 2021)
Some of the main issues that will be discussed in this paper include: 1) the perception that premarital counseling is not important and a waste of time; 2) premarital counseling is carried out only to fulfill the requirements of marriage; 3) premarital counseling is considered an unpleasant way because it talks about personal things.The aim of the study is to show Christians that premarital counseling is important to prepare for lifelong marriage. Starting a family needs to be well prepared through premarital counseling so that each partner knows who he is, what are his weaknesses and strengths in order to become a family that grows in faith and lets go of the old pattern of life so that it becomes a blessing.The method used is qualitative research with the hope of giving the right perspective and attitude about the importance of premarital counseling.